44 new improved high-yielding rice breeding lines for Madagascar (14) and Nepal (30 - CGIAR Research Program on Rice (2019)
• Breeding lines for lowland systems (8 lines) and upland systems (6 lines) submitted for variety registration trials in Madagascar. • 30 breeding lines evaluated under low-input conditions in the hilly region of Nepal • New donors with tolerance to Fe toxicity identified in Madagascar